A new specimen provides insights into the anatomy of Irajatherium hernandezi, a poorly known probainognathian cynodont from the Late Triassic of southern Brazil. Issue 11 (10th December 2021) - Kerber, Leonardo; Martinelli, Agustín G.; Müller, Rodrigo T.; Pretto, Flávio A.
Abstract: Irajatherium hernandezi is a poorly known non‐mammaliaform cynodont from the Late Triassic of southern Brazil. A new specimen of this cynodont was found in recent fieldwork to the type‐locality, Sesmaria do Pinhal (Candelária), providing new insights into the anatomy of this mammalian forerunner. This specimen comprises a partial skull preserving the left canine, two left and three right postcanines, and an isolated exoccipital; the left dentary with the canine and postcanines; a fragment of the right dentary; the proximal portion of the left partial humerus; the right scapula; and indeterminate fragments. Based on new material, it is here suggested that I. hernandezi presents: a rostrum broad and short, possibly long as the temporal region; three foramina on the lateral surface of the maxilla, that could correspond to the external openings of the rostral alveolar, infraorbital, and zygomaticofacial canals; a slender zygomatic arch and an absent postorbital bar; a posteriorly wide temporal fossa; a long secondary palate, slightly surpassing the level of the last postcanine tooth; the cerebral hemispheres of the cranial endocast divided by a median sulcus; the scapular blade long and straight, and the postscapular fossa absent in lateral aspect. Finally, I. hernandezi and other tritheledontids were included in a phylogenetic analysis of Eucynodontia. The analysis recovered unresolved relationships for ictidosaurs/tritheledontids, nested within a polytomy with Tritylodontidae and a clade composed by Pseudotherium argentinus, Botucaraitherium belarminoi, Brasilodon quadrangularis, and Mammaliaformes. Abstract :